Unveiling the Enigmatic Semiotics of Batak Culture in Missing Home Movie - Fitria Aprilia; Wardah Zakiyah; Neisya (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
Culture is one of the lifestyles inherited from generation to generation. This research aims to unveil Batak Toba culture in Missing Home movie by using Barthes’ Semiotic theory since Batak Toba culture is very well-known for its diversity. Descriptive qualitative method through collecting data predominantly in the form of words, images, and other visual or textual representations was used since this research focused on social phenomena and its nature, provide a holistic description or action which was conveyed in the form of words and language for a special context. The object of the research was a movie released in 2022 namely Missing Home. Barthes’ semiotic theory (denotation, connotation and myth) was employed to analyzed the data. Semiotic can be in the form of songs, music notes, dialogue and body movements which in this research Barthes prioritizes 3 main pillars, namely denotation, connotation and myth. This research carried out several concepts with the aim of revealing Barthes' semiotic signs. The sign has been shown through images, dialog, scenes and the background of the movie. Based on the analysis, it was found that there were 7 scenes contained the semiotic meaning (denotation, connotation and myth) from Barthes’ semiotic theory. To conclude, this research can shed light on how cultural symbols, rituals, and traditions are portrayed, provide insights into how cultural elements are interpreted and represented in media, especially within the context of a specific movie.